Biologically rapid synthesis of silver nanoparticles by Sphingobium sp. MAH-11T and their antibacterial activity and mechanisms investigation against drug-resistant pathogenic microbes - Shahina Akter; Md. Amdadul Huq (Artificial Cells, Nanomedicine, and Biotechnology)
The present study highlights the biological synthesis of silver nanoparticles (AgNPs) using Sphingobium sp. MAH-11 and also their antibacterial mechanisms against drug-resistant pathogenic microorganisms. The nanoparticle synthesis method used in this study was reliable, facile, rapid, cost-effective and ecofriendly. The AgNPs exhibited the highest absorbance at 423 nm. The TEM image expressed spherical shape of AgNPs and the size of synthesized AgNPs was 7–22 nm. The selected area diffraction (SAED) pattern and XRD spectrum revealed the crystalline structure of AgNPs. The results of FTIR analysis disclosed the functional groups responsible for the reduction of silver ion to metal nanoparticles. The biosynthesized AgNPs showed strong anti-microbial activity against drug-resistant pathogenic microorganisms. Moreover, Escherichia coli and Staphylococcus aureus were used to explore the antibacterial mechanisms of biosynthesized AgNPs. Minimal inhibitory concentrations (MICs) of E. coli and S. aureus were 6.25 μg/mL and 50 μg/mL, respectively and minimum bactericidal concentrations (MBCs) of E. coli and S. aureus were 25 μg/mL and 100 μg/mL, respectively. Results exhibited that biosynthesized AgNPs caused morphological changes and injured the membrane integrity of strains E. coli and S. aureus. The AgNPs synthesized by Sphingobium sp. MAH-11 may serve as a potent antimicrobial agent for many therapeutic applications.